Effect of fluorometholone (FML) on the intraocular pressure of corticosteroid responders. Issue 8 (August 1984) - Morrison, E; Archer, D B
Abstract : Steroid responsiveness to dexamethasone was determined in a large family with an established dominant form of chronic simple glaucoma. The high and intermediate steroid responders were then tested with fluorometholone--a steroid which is claimed to have a reduced risk of increasing intraocular pressure. It was found that fluorometholone had a much less pronounced ocular hypertensive effect than dexamethasone. However, one patient showed a comparable response on both drugs, and this suggests that some caution must still be exercised when using the drug on susceptible individuals. Fluorometholone was also found to be more irritable to the eye than dexamethasone.